Social isolation, regardless of living alone, is associated with mortality: the Otassha study - Imamura, Keigo; Kawai, Hisashi; Ejiri, Manami; Sasai, Hiroyuki; Hirano, Hirohiko; Fujiwara, Yoshinori; Ihara, Kazushige; Obuchi, Shuichi (Frontiers in Public Health, 2024)
Introduction: Social isolation has been recognized as a contributing factor to negative health outcomes. Although living alone is associated with health-related outcomes, existing findings are inconsistent. It is not the act of living alone that may predict poor health, but rather social isolation that can lead to increased mortality risk. This study investigated the combined associations of social isolation and living alone with mortality among community-dwelling older adults. Methods: We included older adults from Itabashi ward, Tokyo, who participated in comprehensive health checkups. Participants were categorized into four groups based on their social isolation status and living situation. The primary outcome was all-cause mortality, analyzed using Cox proportional hazards models. Results: Of the 1106 participants (mean age 73, 42% male), 4.5% experienced both social isolation and living alone. This combination was associated with a worse prognosis regarding all-cause mortality (hazard ratio (HR): 2.20 [95% confidence interval (CI), 1.17-4.15]). Those who were socially isolated but not living alone also showed a trend toward higher mortality risk (HR: 1.45 [95%CI, 0.92-2.26]). Contrastingly, those who were not socially isolated and lived alone did not show an increased mortality risk (HR: 0.80 [95%CI, 0.44-1.48]). Discussion and conclusion: Living alone is not inherently associated with a poor prognosis in older adults; however, social isolation was associated with a higher mortality risk. Healthcare providers should focus on enhancing social interactions and support for older adults because of their effects on health rather than solely addressing living arrangements to prevent adverse health events.